High-Performance Thermoelectric Polyselenophene/Manganese Oxide Composites - Okcu, Kevser; Ozdogan, Kemal; Huner, Azra (WILEY, 2025)
Polymeric thermoelectric materials (TEs), unlike traditional inorganic TEs, are flexible, low-cost, lightweight, and environmentally friendly, making them attractive for wearable devices, flexible electronics, and low-grade heat harvesting. One of the methods used to prepare the composite of polymeric TEs with inorganic materials is to increase their thermoelectric performance. In this study, the composite of polyselenophene (PSe) with manganese oxide nanoparticles (MnOx) was investigated to improve its thermoelectric properties. For this purpose, PSe was first synthesized by chemical oxidative polymerization in an aqueous medium. Then, MnOx was synthesized. In the next step, in situ hybrid composites of PSe and MnOx (PSe/MnOx) were synthesized, and thin films were prepared from these composites. These synthesized materials were characterized by UV-Vis, FTIR, TGA, XRD, SEM, and EDS analyses. Thermoelectric properties of the prepared thin films were examined. When the amount of MnOx by mass compared to PSe was increased from 5% to 20%, the Seebeck coefficient increased from 31 to 489 mu V K-1. The PSe/MnOx3 composite with 20% MnOx had the highest Seebeck coefficient and power factor, measuring 489 mu V K-1 and 2.39 x 10-2 mu W m-1 K-2, respectively.
Keywords: composites; conducting polymers; films; seebeck coefficient; POWER-FACTOR; OPTIMIZATION; COPOLYMERS; PEDOT; Polymer Science